Heavy metal distribution in the bottom sediments along Tietê River Basin - Mortatti, Jefferson; Hissler, Christophe; Probst, Jean-Luc (Geologia USP. Série Científica, 2010)
Analysis of heavy metals in fluvial sediments has been used to better understand the potential hazards and critical toxicity of heavy metals mainly related to the anthropogenic influences of urban sewage, industrial effluents and agricultural activity. The present study analyzed the heavy metals, such as Cr, Cu, Ni, Zn and Pb, in the bottom sediments along the Tietê River basin, a polluted watershed in the Southeast region of Brazil. The distribution of the concentrations of heavy metals in the upper basin decreased in the following order: Zn >; Cr >; Pb >; Ni >; Cu, whereas, in the middle part of the basin (which is under strong urban and industrial influences), high concentrations of Zn, Cu and Cr were observed, measuring 648, 200 and 183 μg g-1, respectively. The sequential chemical extraction in relation to the total concentration was used to assess the potential bioavailability of heavy metals. In the upper part of the basin, the heavy metals extracted from the bottom sediments were mainly related to the residual fraction, whereas, in the middle part of the basin, the bioavailability of Zn, Cr and Ni was higher than 60%, and these metals were mainly related to the iron oxide phase. The high concentration of heavy metals observed in the middle basin of the Tietê river (after the metropolitan area of São Paulo), when compared with the average concentration found in the geochemical bottom, showed that, in terms of enrichment factor and geoaccumulation index, the degree of pollution by Zn is high and by Ni is high to moderate in the downstream direction.